1993
DOI: 10.1111/j.1469-8986.1993.tb02079.x
|View full text |Cite
|
Sign up to set email alerts
|

Pictures as prepulse: Attention and emotion in startle modification

Abstract: The effects of an emotional stimulus prepulse on probe startle response were examined here. Pleasant, neutral and unpleasant pictures were viewed for 6 s, and an acoustic startle probe was presented either 300, 800, 1,300, or 3,800 ms after slide onset, or 300 or 3,800 ms after slide offset. Blink magnitude and onset latency demonstrated (a) an early (prepulse) inhibition effect in which reflexes elicited immediately after slide onset were smaller than reflexes elicited later in the viewing interval, and (b) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
186
4
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(209 citation statements)
references
References 11 publications
15
186
4
4
Order By: Relevance
“…Sokolov (1963) first described a shift from an orienting to a defense response when a tone of increasing intensity was presented. Recent studies used the startle reflex paradigm to examine both attentional and valence motivational mechanisms during presentation of emotional slides (Bradley, Cuthbert, & Lang, 1993). Consistent with our results, Cuthbert et al (1996) showed that low-arousal negative slides elicited a smaller startle response (indicating a larger attentional activity because startle reflex is proportionally inhibited by attentional engagement) than did positive slides.…”
Section: Physiological Resultssupporting
confidence: 89%
“…Sokolov (1963) first described a shift from an orienting to a defense response when a tone of increasing intensity was presented. Recent studies used the startle reflex paradigm to examine both attentional and valence motivational mechanisms during presentation of emotional slides (Bradley, Cuthbert, & Lang, 1993). Consistent with our results, Cuthbert et al (1996) showed that low-arousal negative slides elicited a smaller startle response (indicating a larger attentional activity because startle reflex is proportionally inhibited by attentional engagement) than did positive slides.…”
Section: Physiological Resultssupporting
confidence: 89%
“…These mechanisms confer evolutionary advantages, as unattended fearrelevant stimuli may be partially processed to prepare the organism for the occurrence of a potentially aversive situation. A number of behavioural and psychophysiological studies showing encoding biases for threat-related information are likely to reflect the operation of such initially preattentive processes [4,13,31,37,47,53]. Recently, a behavioural study by Holmes and colleagues [37] showed that rapid attentional responses to fearful versus neutral faces were driven by LSF rather than HSF visual cues, in line with the role of amygdala and orbitofrontal cortex in the mediation of attention towards threatening faces.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, we expected the high arousal pleasant and unpleasant conditions to elicit greater SCR amplitude than the corresponding low arousal conditions (Bradley et al, 1993;Lang et al, 1993a). SCRs were recorded with two Ag/Cl electrodes on the left palm.…”
Section: Skin Conductance Responsesmentioning
confidence: 99%